USING THE EXPERIENCE OF TRAINING MILITARY PERSONNEL IN THE UNITED STATES TO ADVANCED TRAINING OF OFFICERS OF THE ARMED FORCES OF UKRAINE AND OTHER MILITARY FORMATIONS - Артюшин, Г. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2019)
The article deals with the problem of modernization of the training system for officers training of the Armed Forces of Ukraine and other military formations in the context of the modern strategic tasks of the development of the Armed Forces of Ukraine. The peculiarities of modern training of servicemen in the USA are highlighted and possible aspects of the use of this experience in the system of professional development of officers of the Armed Forces of Ukraine and other military formations. It is revealed that the existing system of training of servicemen in Ukraine does not fully meet the modern requirements and requires comprehensive modernization, which requires the study and implementation of advanced foreign experience in the training of officer personnel. The advantages of the military education system of the USA as one of the most powerful systems of military personnel training in the modern world are determined: the branch network of educational institutions providing training and advanced training of officer personnel at different stages of training according to the types of troops; systematic, phased and multi-level training, and advanced training; efficiency and dynamism; a combination of theoretical and practical training, civil and military education, teaching and research work; prestige, competitiveness and high efficiency. The urgent tasks of modernization of higher military education are defined taking into account the US experience: the transition to a professional army, introduction of modern standards of military activity, increase of flexibility and diversity of military education, increase of dependence of career growth on the level of qualification of servicemen, improvement of the structure of training of troops, attraction to teaching highly skilled , experienced military specialists, trainers (instructors) on highly specialized subjects, strengthening of scientific about maintenance of educational process, introduction of modern information technologies